Thrones & bones : frostborn - Anders, Lou (Scholastic, 2014)
Destined to take over his family farm in Norrøngard, Karn would rather play the board game, Thrones and Bones, until half-human, half frost giantess Thianna appears and they set out on an adventure, chased by a dragon, undead warriors, an evil uncle, and more.